2015
DOI: 10.1136/bmjopen-2014-006815
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose intra-articular bupivacaine plus morphine after knee arthroscopic surgery: a meta-analysis of randomised placebo-controlled studies

Abstract: ObjectivesTo evaluate the efficacy and safety of single-dose intra-articular bupivacaine plus morphine after knee arthroscopic surgery.DesignMeta-analysis.Data sources and study eligibility criteriaA comprehensive literature search, using Medline (1966–2014), the Cochrane Central Register of Controlled Trials and Embase databases, was conducted to identify randomised placebo-controlled trials that used a combination of single-dose intra-articular bupivacaine and morphine for postoperative pain relief.Results12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The single-dose intra-articular (IA) analgesic agents has been widely used for pain relief after arthroscopic surgery as a simple and economical approach. Previous meta-analyses have demonstrated that the single-dose IA morphine34, bupivacaine567, ropivacaine8, clonidine9 or the combination of morphine and bupivacaine1011 were effective in pain relief. However, it is commonly known that IA local anesthetics must be used cautiously due to the concern of chondrotoxicity12, especially for bupivacaine13141516171819, levobupivacaine131419, ropivacaine13141617, mepivacaine17 and lidocaine13161820.…”
mentioning
confidence: 99%
“…The single-dose intra-articular (IA) analgesic agents has been widely used for pain relief after arthroscopic surgery as a simple and economical approach. Previous meta-analyses have demonstrated that the single-dose IA morphine34, bupivacaine567, ropivacaine8, clonidine9 or the combination of morphine and bupivacaine1011 were effective in pain relief. However, it is commonly known that IA local anesthetics must be used cautiously due to the concern of chondrotoxicity12, especially for bupivacaine13141516171819, levobupivacaine131419, ropivacaine13141617, mepivacaine17 and lidocaine13161820.…”
mentioning
confidence: 99%
“…Previous meta-analyses showed that single-dose IA morphine, 5 bupivacaine, 6 bupivacaine plus morphine, 9 ropivacaine 7 and magnesium 29 were effective for postoperative pain management in patients undergoing arthroscopic knee surgery without increasing any adverse reactions. However, no systematic and comprehensive comparison has been reported yet regarding the safety and efficacy of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Single-dose intra-articular (IA) analgesics have been widely used for pain relief after arthroscopic knee surgery as a simple and economical technique. Several meta-analyses have assessed the efficacy and safety of commonly used single-dose IA analgesics, including morphine, 5 bupivacaine, 6 ropivacaine, 7 magnesium 8 or the combination of morphine and bupivacaine, 9–11 and the conclusions have provided important guidance to clinical practice. However, determination of the safest and the most effective option is still a challenge because the comparative efficacy and safety of these analgesics remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, intra-articular morphine has been shown clinically to improve pain scores and decrease the need for supplemental postoperative narcotics, with enhanced efficacy when used in combination with local anesthetics for patients undergoing anterior cruciate ligament (ACL) reconstruction. 13 , 16 , 24 , 27 , 30 , 32 …”
mentioning
confidence: 99%
“…Additionally, intra-articular morphine has been shown clinically to improve pain scores and decrease the need for supplemental postoperative narcotics, with enhanced efficacy when used in combination with local anesthetics for patients undergoing anterior cruciate ligament (ACL) reconstruction. 13,16,24,27,30,32 Despite these benefits, the intra-articular injection of morphine fell out of favor with the rise of peripheral nerve blocks. Early literature indicated that peripheral nerve block was more efficacious; however, these studies were limited by the use of continuous peripheral nerve blocks and the absence of morphine in their intra-articular injection cocktail.…”
mentioning
confidence: 99%